Mechanical, electrochemical and multifunctional performance of a CFRP/carbon aerogel structural supercapacitor and its corresponding monofunctional equivalents. Issue 2 (1st June 2022) - Pernice, Maria Francesca; Qi, Guocheng; Senokos, Evgeny; Anthony, David B; Nguyen, Sang; Valkova, Maria; Greenhalgh, Emile S; Shaffer, Milo S P; Kucernak, Anthony R J
Abstract: This work investigated and developed a protocol for establishing the multifunctional performance of a structural supercapacitor: a composite which can simultaneously carry mechanical load whilst storing electrical energy. The Structural Supercapacitor consisted of carbon aerogel (CAG) reinforced carbon fibre electrodes which sandwiched a woven glass fibre lamina and was infused with a structural electrolyte (SE). This was compared to two monofunctional devices: a Monofunctional Supercapacitor and a Monofunctional Laminate in which the SE had been replaced by ionic liquid and a structural epoxy, respectively. In the Monofunctional Supercapacitor, the considerable surface area of the CAG and ionic capacity of the liquid electrolyte resulted in a high device normalised capacitance (1731 mF g −1 ). However, in the Structural Supercapacitor the SE presented meso-scale heterogeneity, obstructing the CAG pores with thin films of epoxy. This resulted in a considerable reduction in electrochemical performance, with a drop in the device normalised capacitance to 212 mF g −1 . Regarding mechanical performance, it was shown that the CAG had promoted brittle fracture, leading to a severe depression in the tensile and in-plane shear strengths. The Structural Supercapacitor presented a tensile modulus and strength of 33 GPa and 110 MPa, respectively: a 15% and 11% drop in tensile modulus and strength, respectively, compared to that of the Monofunctional Laminate . However, under in-plane shear the soft SE dominated, leading to about a 44% drop in shear modulus (1.7 GPa) and strength (13.7 MPa at 1% shear strain). This work has provided an insight into the hurdles associated with demonstrating multifunctionality, including the scaling challenges for electrochemical and mechanical characterisation and the need to report both active material and device normalised data. The emergence and development of such structural power composites could address the issue of parasitic battery mass in transportation, and hence realise full electrification of aircraft and cars.